Improving the Efficiency of Wireless Multi-Hopping of MPEG-4 AVC Video Stream in WAN - Rajesh Kumar, S (International Journal of Computer Sciences and Engineering, 2015)
Video streaming has become the application that drives the Internet to a new height. In this paper, we analyze and evaluate the performance of H.264-based video streaming over multi-hop wireless local area networks (WLANs). Contrary to common believes that adding relays in the same wireless channel may increase coverage but has to reduce throughput, our analysis and simulation results show a wide spectrum of coverage-capacity tradeoff in generic scenarios and confirm previous measurement observation in specific cases.